Growing Up Urban: Hyena Foraging Groups and Social Structure at a City Waste Dump - Struller, Franziska; Bauer, Hans; Yirga, Gidey; Vos, Matthijs (Frontiers in Conservation Science, 2022)
Urban spotted hyenas (Crocuta crocuta) in Ethiopia are a prime example of large carnivores coexisting with little to no conflict with people in a human-dominated landscape, providing a valuable waste-removal service. To gain insight in how this urban lifestyle persists across generations, we studied hyena group composition at the city waste dump of Mekelle, a regional capital in northern Ethiopia. We found that hyena cubs and sub-adults foraged with adults in groups of highly variable composition. Young urban hyenas already take part in a fission-fusion dynamic that is also characteristic of hyenas in non-urban environments. They do not seem to learn from only one or few close reference adults. Social network analysis revealed no clusters among these dump-visiting hyenas. The number of counted hyenas is furthermore larger than any hyena clan in non-urban areas. All individuals were more or less equally connected to each other, and each hyena had a few connections, but to different individuals. All cubs and sub-adults were connected to each other, over a maximum of four links. Hyenas shared the abundance of food at the waste dump without overt aggression. A much larger number of urban hyenas shares this waste dump at night than would fit into a single forest fragment, such as those associated with orthodox churches where small groups of hyenas have often been observed to rest at daytime. Hyenas appear to commute from different dens and resting sites located around the city, but we have no information on their behavior and group composition away from the dump. We observed no defense of any part of the dump area by any of the foraging groups. In absence of territorial behavior at this city site, the clan concept does not seem to apply to these urban hyenas. Similar to what has been observed in other urban carnivores, individuals at the waste dump behaved as members of conflict-free foraging groups ostensibly sharing food without aggression. Perhaps this is what most strikingly defines their urbanity.